Structural behaviour of novel composite beams consisting of geopolymer concrete and high-performance concrete - Nikbakht, E. (Elsevier Ltd, 2021)
Over the past few years, geopolymer concrete (GPC) has experienced increasing demands in construction technology thanks to its numerous advantages, such as being eco-friendly and highly resistant to elevated temperatures and chemical attacks in aggressive environments. However, similar to normal concrete, GPC has limited tensile strength and deformation capacity. High-performance concrete (HPC) exhibits high flexural strength and enhanced mechanical properties, such as tensile strength. In this study, novel hybrid beams consisting of GPC at the compression zone and HPC at the tension zone are explored and investigated. The mechanical properties of GPC and HPC as well as the structural behaviour of hybrid beams consisting of two different layers of GPC and HPC with different ratios (50 to 50, 75 to 25) are also investigated. Moreover, full-depth beams consisting of single layer of either GPC or HPC are cast and tested as the control specimens. In addition, the structural behaviour of beams with and without shear reinforcement in terms of shear strength, crack patterns, failure modes, ductility, and energy absorption is investigated. As shown by the results, compared to full-depth GPC and HPC beams, hybrid composite beams without shear reinforcement exhibit low ultimate strength mainly because of the large debonding between the GPC and HPC layers. However, hybrid beams with shear reinforcement exhibit high stiffness, shear strength, and ductility, especially hybrid beams with a GPC-to-HPC ratio of 50 to 50, which demonstrate full composite actions between the GPC and HPC and as a result exhibit high ductility and deformation capacity. Â© 2021